Food beyond the city – Analysing foodsheds and self-sufficiency for different food system scenarios in European metropolitan regions. (March 2019) - Zasada, Ingo; Schmutz, Ulrich; Wascher, Dirk; Kneafsey, Moya; Corsi, Stefano; Mazzocchi, Chiara; Monaco, Federica; Boyce, Peter; Doernberg, Alexandra; Sali, Guido; Piorr, Annette
Abstract: The debate on urban resilience and metabolism has directed increasing attention to the ecological footprint of food consumption, self-sufficiency as a means of food security, and regionalisation of food systems for shortening supply chains. Recently, metropolitan regions have proposed food policies that aim to foster local food systems connected to their cities. Our research thus focused on the relationship between urban food demand and metropolitan land use. We have developed the Metropolitan Foodshed and Self-sufficiency Scenario (MFSS) model, which combines regional food consumption and agricultural production parameters in a data-driven approach to assess the spatial extent of foodsheds as well as the theoretical self-sufficiency of the communities they serve. The model differentiates between food groups, food production systems, levels of food loss and waste as well as food origin. With regard to future urban growth, we applied the model to current and future population projections. Results show substantial variations in the spatial extent of metropolitan foodsheds and self-sufficiency levels between the case study regions London, Berlin, Milan and Rotterdam, depending on population density and distribution, geographical factors and proximity to neighbouring urban agglomerations. The application of the model as a food planning tool offers a new perspective on the potential role of metropolitan regions for strengthening urban self-sufficiency. It also enables the ex-ante assessment of spatial consequences of changes within metropolitan food systems, on both demand and supply sides. In particular, we discuss possible dietary and consumption changes, but also production and supply chain alternatives. Highlights: A spatial model to depict metropolitan foodsheds and self-sufficiency is proposed. Scenarios of changing food demand and supply are applied. Regional situations indicate different food stress, especially for future population growth. Increasing area demand by organic production can be balanced by food waste reduction.